1976
DOI: 10.1152/ajplegacy.1976.231.2.516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the histamine (H2) inhibitor metiamide on histamine-stimulated bile flow in dogs

Abstract: The effects of the histamine H2-receptor inhibitor metiamide on histamine-stimulated canine bile flow and gastric hydrogen ion output were evaluated. Histamine was found to stimulate bile volume in doses comparable to those that stimulated gastric hydrogen ion output; both responses appeared to have the same maximal response dose, 150 mug/kg per h. Metiamide alone did not alter hepatic bile flow. Administration of metiamide, 2 mg/kg per h, along with various doses of histamine demonstrated that the H2-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…A constant degree of inhibition in the presence of increasing doses of agonist (histamine) strongly suggested that the antagonists (cimetidine and ranitidine) were not competing with the agonist for receptor sites, indicating noncompetitive inhibition. Similar conclusions were drawn by Kaminski et al (1976) using another H2-antagonist, metiamide. The concomitant infusion of diphenhydramine, an HI-antagonist, enhanced the inhibitory action of small doses of either cimetidine or ranitidine.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A constant degree of inhibition in the presence of increasing doses of agonist (histamine) strongly suggested that the antagonists (cimetidine and ranitidine) were not competing with the agonist for receptor sites, indicating noncompetitive inhibition. Similar conclusions were drawn by Kaminski et al (1976) using another H2-antagonist, metiamide. The concomitant infusion of diphenhydramine, an HI-antagonist, enhanced the inhibitory action of small doses of either cimetidine or ranitidine.…”
Section: Discussionsupporting
confidence: 76%
“…The choleretic effect of histamine, although a new finding in the sheep, has been reported previously in the dog (Jones & Grossman, 1969;Kaminski, Ruwart & Jellineck, 1976). Histamine most probably directly stimulated bile flow since gastrectomized dogs (without any secretin release) also responded to histamine.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the same study the amounts of pancreatic and biliary secretion were unaffected by either the cimetidine or the reduced acid load in the duodenum. However, hista mine stimulates bile tlow and this is blocked (noncompetitively) by metia mide (45).…”
Section: Gastric Secretion In Ma Nmentioning
confidence: 99%